Current and paleoclimate models for an Atlantic Forest kissing bug indicate broader distribution outside biome delimitations - Corrêa-do-Nascimento, Guilherme Sanches; Leite, Gustavo Rocha (Frontiers in Ecology and Evolution, 2023)
Rhodnius domesticus (Neiva & Pinto, 1923) is a kissing bug considered the only endemic species of the Atlantic Forest for the Rhodniini tribe. In this study, we aim to indicate species trends of paleodistribution, exploring the connections with neotropical areas from the last maximum glacial to the current time and paleodistributions in the continental shelf. We revised Rhodnius domesticus distribution information and created ENMs between the current time and Pleistocene end scenarios for the study regions. Models were built and validated using Maxent, KUENM, and ENMeval packages in R and ArcMap. Environmental data used are available in PaleoClim online dataset. We considered models' uncertainty when calculating average model variance and using MOP analyses. We found 44 different geographical species records, and our current time models indicate suitable areas in coastal regions of the Atlantic and surrounding locations in higher and lower latitudes. Paleoclimatic models indicate general suitability in coastal regions and change in suitability in the interior region through time. Our revision and ENMs indicate seven main points: (1) R. domesticus records are spatial and time concentrated in some coastal regions of the Atlantic Forest. (2) Data supports occurrence outside Atlantic Forest delimitations in Northeast and southwest areas of South America. (3) Models do not falsify the possible synonymy with Rhodnius zeledoni. (4) R. domesticus paleodistribution was stable in Atlantic coastal regions, with significant distribution on the continental shelf. (5) The species could have dispersed and established significant populations in the northeast regions of South America at the Pleistocene end and decreased to become scarce populations in current scenarios. (6) R. domesticus suitability areas indicate a possible connection to the Amazon by the northeast route in the Pleistocene end and development of the southeast-northwest route region into the Anthropocene. (7) The species could have conserved ancestral niches from Amazonian areas.